Measurement of Kidney Function of Wistar Rats treated with Ethanol Leaf Extract of Justicia schimperi (Acanthaceae) - Etim, O. E.; Ewere, E. G.; Uka, E. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Over the years, several plants have been reported to be of immense medicinal value in the treatment and management a number of disease conditions. In this study, the effect of ethanol extract of Justicia schimperi on kidney function of albino wistar rats was investigated. 30 matured male and female albino rats were used for the study. The rats were divided into five groups of six animals per group. Group 1 served as control and was administered with rat pellets and water ad libitum. Groups II, III, IV, and V were treated with 273.8mg/kg, 547.7mg/kg, 821.5mg/kg, and 1095.4mg/kg bw of ethanolic extract of Justicia schimperi respectively for 14 days. The rats were sacrificed on the 15th day after 12 hours of fasting and serum obtained and analyzed for the level of creatinine, urea, sodium, bicarbonate, potassium and chloride. The results revealed that groups 3, 4 and 5 showed significant (p< 0.05) increases in all the parameters assayed when compared to control except sodium level for group 4. Ethanol leaf extract of Justicia schimperi in the present study appear to increase the levels of electrolytes, creatinine and urea. Therefore care must be applied in consumption of the leaf.